Jan z Czarnkowa o zajęciu zamku w Uniejowie w 1381 roku - Pastwiński, Zbigniew (Biuletyn Uniejowski, 2014)
The article recounts the story of the killing of the administrator of Uniejów castle, provost of Kurzelów Pełka, by Mikołaj of Grabów, the castellan of Łęczyca, during a feast organized by the governor of Łęczyca, Piotr Kmita, in Dąbie on the river Ner. As a result of the killing, Pełka’s brother Bernard of Garbów occupies the archbishop’s castle in Uniejów and plunders it. The starost of Greater Poland, Domarat of Pierzchno, undertakes intervention which leads to an agreement that in return for leaving the castle he can keep the loot and go away free. The author provides descriptions of the heroes of those events and of the general situation in Greater Poland during the reign of Louis I of Hungary.